A Study to Evaluate Relationship between Anxiety Depression and Glycemic Control among Type 2 Diabetes Mellitus Patients - Rahimoon, Muhammad; Channar, Husan Bano; Mansoor Syed, Binafsha; Raza, Saad; Munwar Us Salam; Jabbar, Abdul (Indus Journal of Bioscience Research, 2024)
Background: Diabetes Mellitus is one of the most widespread disorders in public health, requiring careful glycemic control to prevent complications. Alongside physical challenges, DM patients often experience psychological distress, particularly anxiety and depression, which can further complicate diabetes management and influence psychological well-being, and diminish the quality of life of individuals. Aim of study: To evaluate the relationship between anxiety, depression, and glycemic control among Type 2 Diabetes Mellitus patients. Material and Methods: A descriptive cross-sectional study was conducted on 301 Type 2 Diabetes Mellitus patients at Liaquat University Hospital Hyderabad, Sindh, Pakistan from May 2024 to October 2024. Non-probability-purposive sampling technique was used to collect data. Anxiety and depression levels were measured using the GAD-7 and PHQ-9 scales, respectively. HbA1c level was used to assess glycemic control. Data was analyzed using SPSS 26.0; Descriptive analysis including mean, frequency, percentage, and standard deviation was used along with the Fisher test to analyze significant relationships. Results: Among the 301 T2DM patients, 52.49% were male with a mean age of 46.16 years. Most participants lived in urban areas (69.44%) and 50.5% were intermediate or below in education. Most of the participants (73.09%) were unemployed, and 96.7% were married. In terms of glycemic control (GC), 76.74% of participants had poor glycemic control (HbA1c ≥ 7.1). Individuals with poor glycemic control demonstrated significantly higher levels of anxiety (p < 0.009) and depression (p < 0.016). Conclusion: Poor glycemic control is strongly linked to increased anxiety and depression in T2DM patients. These findings highlight the need for incorporating mental health screening and interventions into diabetes care to improve both psychological and physical health outcomes